Automated modeling of nickel‐based superalloys. Issue 1 (15th March 2018) - Munk, Lukas; Beese, Steffen; Reschka, Silvia; Wriggers, Peter
Abstract: Throughout the last 60 years, nickel (Ni) based superalloys have been the standard high‐temperature material used in mobile and stationary gas turbines. The ever increasing temperatures necessitate further improvements of those alloys, foremost, enhancing their creep‐resistance. Creep denotes a macroscopic, permanent change of shape which, amongst other effects, stems from thermally and mechanically induced dislocation movement. The key microstructural feature of most modern alloys is a uniform distribution of particles of the L 12 ‐ordered γ′ phase which are embedded into the nickel‐based matrix. Most importantly, these particles are impenetrable to matrix‐dislocations. This leads to numerous dislocation effects encountered in such microstructured alloys. A wealth of different material modeling‐approaches exists in the literature which try to capture creep behavior. Due to the multiscaled nature of the physical problem, most crystal plasticity approaches are phenomenological and, thus, rely on many parameters. Finding suitable constitutive equations that capture experimental results becomes a challenge. A large deformation crystal plasticity framework has been set up which allows for an efficient comparison of different material formulations. This has been achieved by the use of AceGEN. The analytically generated tangent‐subroutine is linked into a FEAP polycrystal plasticity model and thus, global quadratic convergence is reached. In future work, a variety of flow rules, dislocation density based (cross‐) hardening formulae and parameters can be studied in a unified way [6]. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)